Whole-Genome Sequence of the Cheese Isolate Lactobacillus rennini ACA-DC 565 - Kazou, Maria (Genome Announc, 2017)
In this study, we present the first complete genome sequence of Lactobacillus rennini ACA-DC 565, a strain isolated from a traditional Greek overripened Kopanisti cheese called Mana. Although the species has been associated with cheese spoilage, the strain ACA-DC 565 may contribute to the intense organoleptic characteristics of Mana cheese.